Kinetic study of the utilisation of different substrates to lactic acid using Lactobacillus delbrueckii - A Abdullah; Hanapi bin Mat; W Widayat (Jurnal Teknik Kimia Indonesia, 2005)
AbstractLactic acid fermentation includes several reactions in association with the microorganism growth. A kinetic study was performed of the utilisation of multiple substrates to lactic acid using Lactobacillus  delbrueckii. Batch fermentation was performed to study effect of different substrates such as glucose, fructose and sucrose. The objective of this research is to study kinetics grow microbial. An anaerobic fermentation were studied in 3 litres stirred fermentor (Biostat B Model) with working volume of 1 liter: temperature = 40ºC, pH=6.0, inoculums size= 5%, sugar concentration= 20 g/L. During the first hours of fermentation, glucose and fructose accumulated in the medium and the rate of hydrolysis of sucrose to glucose and fructose was faster than conversion of these substrate. The maximum concentration of glucose and fructose was 5.82 and 5.14 g/L respectively. The sucrose, glucose, and fructose consumption completely utilized at 56, 68, and 104 hours, respectively. Kinetic parameter for maximum specific growth rate in glucose, fructose and sucrose is 0.083, 0.024, and 0.024 (h-1), respectively. The saturation constant is 4.64, 3.41, and 1.36 g/L.Keywords: Kinetic Study, Sugars, Lactic Acid, Maximum Specific Growth Rate, Saturation Constant AbstrakFermentasi asam laktat melibatkan banyak reaksi dalam pertumbuhan mikroorganisme. Studi kinetika reaksi tentang kinerja penggunaan berbagai subtrat untuk memproduksi asam laktat dengan Lactobacillus delbrueckii.Subtrat yang digunakan adalah glukosa, fruktosa, dan sukrosa, dengan proses fermentasi curah. Penelitian ini bertujuan memepelajari kinetika pertumbuhan mikroba. Fermentasi anaerobik dilakukan dalam fermentor 3 liter (Biostat B Model) dengan volume total 1 liter, temperatur = 40ºC, pH= 6.0, konsentrasi inokulum = 5%, konsentrasi gula = 20 g/L. Selama satu jam pertama fermentasi, glukosa dan fruktosa diakumulasi dalam medium dan laju reaksi hidrolisis sukrosa menjadi glukosa dan fruktosa sangat cepat dibandingkan dengan konversi substrat ini. Konsentrasi glukosa dan fruktosa adalah 5.82 dan 5.14 g/L. Waktu yang dibutuhkan sukrosa, glukosa dan fruktosa masing-masing adalah 56, 68, dan 104 jam. Parameter kinetika untuk laju pertumbuhan spesifik maksimum dalam medium glukosa, fruktosa, dan sukrosa masing-masing adalah 0.083, 0.024, dan 0.024 (h-1). Konstanta saturasi adalah 4.64, 3.41, dan 1.36.Kata Kunci:  Kinetika Reaksi, Gula, Asam Laktat, Laju Pertumbuhan Spesifik Maksimum, Konstanta Saturasi